IMPLEMENTASI VIRTUALISASI SERVER BERBASIS PRIVATE CLOUD COMPUTING MENGGUNAKAN PROXMOX VIRTUAL ENVIRONMENT (VE) - Vadreas, Andrew Kurniawan (Lembaga Penelitian Dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2016)
The planning of activity of school operational at SMK N 1 Lembah Melintang the which is based information technology need to a server as one of the support facilities. There are many server applications are Needful roomates, therefore it is has a need of a specific management to manage the server. In addition to the network infrastructure at SMK N 1 Lembah Melintang is limited to the development of a server because of the unavailability of the server in the network serving the information systems and storage and sharing of data together. Tus, using service of private cloud computing; virtualization of servers can make-out the problem. Virtualization is a technique of management systems and resources functionally by hiding physical characteristic of resources. The virtualization concept is possible some servers are running on the machine. Proxmox Virtual Environment is a specific operation system of virtualization that can be entranced some virtual servers. The main advantage of virtualization is for decreasing operational cost of the server hardware to invest. By building a virtualization server with private IP can use the same IP on the local area network (LAN) in SMK N 1 Lembah Melintang to access the cloud server, web server, ftp server, whereas for access from outside the firewall dstnat technique was used.